Çok katlı yapılarda geri çekme düzensizliğinin deprem hesabına etkisi - Yalçın, Kubilay (Fen Bilimleri Enstitüsü, 1997)
Yüksek lisans tezi olarak sunulan bu çalışmada düşey geometrik düzensizliklerden biri olan ve 'Geri çekme düzensizliği' olarak isimlendirilen problemin deprem hesabına olan etkisi konusu araştırılmıştır. Hemen hemen tüm çağdaş deprem yönetmeliklerinde olduğu gibi ABYYHY-1996 da da yer alan bu düzensizliğin tanımı genellikle yapının geometrik boyutlarına bağlı bazı kriterlerle verilmekte ve çözüm olarak dinamik analiz önerilmektedir. Yapısal düzensizliklerin çoğunda bir yaptırım olarak ortaya konan dinamik analiz önerisinin tüm yapılarda amacına ulaştığı şüpheli gözükmektedir. Bu durum geri çekme düzensizliğinin daha somut bir biçimde tanımlanması zorunluluğunu getirmiştir ve tez çalışmasının araştırma konusunu oluşturmuştur. Çalışmada [4] numaralı yayında yer alan yapısal düzensizliklerinin incelenmesi için geliştirilen parametrik bir 'Sayısal Deney' yöntemi kullanılmıştır. Uygulamalar için farklı boyut ve rijitliklere sahip sekiz, onaltı ve yirmidört katlı çeşitli örnekler ele alınmıştır. Her yapı modeli belirlenen yöntem ile ayrı ayrı incelenmiş ve elde edilen sonuçlar değerlendirilmiştir. Böylece, Geri Çekme Düzensizliği olarak isimlendirilen bu yapısal düzensizliğin tanımı ve ortaya çıkan sorunların çözümü için yeni bir görüş verilmeye çalışılmıştır.

This study that is submitted as Master Thesis, consists of the investigations on Set- Back buildings in Multi-Story Structures. in the first chapter, the scope and the aim of the subject are introduced. in the last decade, the design and construction of tali buildings become more popular in our country, specially in majör cities. The increase on the usage of multi-story buildings caused problems on their analysis and design. The most important matter is the resistance and behaviour of the buildings under lateral loads. The behaviour of a multi-story building during strong earthquake motions depends on the distributions of mass, stiflhess and strength in both the horizontal and vertical planes of the building. Structural engineers have developed confidence in design of buildings in which these distributions are more ör less uniform. Engineers are less confîdent about the design of structures having irregular distributions. A type of irregular structure for which some performance has been observed during past earthquake is the Set-Back building. Set-Back buildings become more popular, due to the architectural requirements and structural obligations. A Set-Back building is considered to be a sudden change in plan dimension ör a sudden change in stifBıess along the height of a building. Many investigations have been performed to attempt to understand the behaviour of set-back buildings and to ascertain methods of improving their performance. By considering the facts above, in most seismic contemporary regulations and codes for buildings, structural irregularities both in plan and elevation like set-back buildings are required to be taken into consideration in earthquake resistant design procedures. For this reason, instead of the Turkish Seismic Code-1975 that became insuflficient due to the new structural design technologies, the New Turkish Seismic Code was published in May 1996. XV In the codes of the different countries, structural irregularities in horizontal and vertical directions are evaluated. Due to this reason, new chapters on the structural irregularities and their solutions were attached to the 'ABYYHY,1996' Turkish Seismic Code. The definition of the Set-Back buildings in ABYYHY-1996 is given by some criteria that depend only on the geometrical dimensions of the structure. But this definition is not enough, because the set-back irregularity depends on several other factors. In ABYYHY-1996 and almost in all seismic codes, 'Dynamic Analysis' is demanded of set-back irregularity, which is considered as a punitive measure. However, in many cases, the punitive nature of 'Dynamic Analysis' seems rather doubtful and is open for discussion. This discussion constitutes the main theme of this Master Thesis. In this way, the clauses about the set-back irregularity in ABYYHY- 1996 (the Turkish Code on Earthquake Design that became valid in 1996 is being examined for a period of one year) which are not applicable or reasonable, can be changed accordingly. In this study, set-back irregularity is examined by applying a numeric test procedure on a number of structures and the results are evaluated. In each case typical multi story structures are chosen and analysed by using equivalent static loads that are computed according to the latest 'Turkish Seismic Code' regulations. The results are then compared to those obtained by the method of 'Modal Superposition' and the necessity of 'Dynamic Analysis' is discussed. By considering the facts above, a research project on the 'Investigations on Vertical Structural Irregularities in Multi-Story Structures' has been started under the sponsorship of Turkish Scientific and Technical Research Council. This thesis is a part of this research project. In the second chapter of the thesis, the analysis methods of multi-story buildings under earthquake loading have been studied. The methods used to obtain the internal forces due to earthquake effects in multi-story buildings are as follows :. Dynamic analysis methods. Semi-dynamic analysis method. Static analysis method The time increment and modal superposition methods are used widely as dynamic methods. The semi-dynamical method is proposed in most codes due to its variable results in most conditions and its simplicity. This method is named as 'Equivalent Static Load' method. Nowadays, the third method, namely the static analysis method, is not used. XVI The results of the second chapter show that the dynamic analyses of structures are very difficult and tedious for most structures. For this reason most of the countries prepared their earthquake codes according to the geographical and structural technological conditions. These codes contain practicable solution techniques of structures against dynamic effects. The third chapter is devoted to the codes on earthquake design. This chapter includes the parts of the abstract of 'ABYYHY,1996' Turkish Code on Earthquake Design relevant to the discussion topics of this study. The damages after earthquake raised the need for some regulations in earthquake resistant design. Accordingly, the regulations, named as Earthquake Codes, were improved specially after San Francisco (1906), Messina-Reggio (1903) and Tokyo (1923) earthquakes. The studies after these earthquakes, show the well design and wooden framed structures are more durable than others. These results were combined and published firstly in Uniform Building Code in 1927 after Santa Barbara (1925). In our country, the first seismic code was published in 1940. Depending on the developments in the earthquake design some codes were published in different years. Finally, the last code called ABYYHY that responds to nowaday's condition was published in 1996. In the fourth chapter, the resistant of buildings to earthquake loads is explained. In the second part of this chapter, the regular and irregular buildings are defined. Structures designed in conformance with their provisions should be able to resist moderate earthquakes without significant damage and major earthquakes without collapse. In the fifth chapter, the set-back irregularity that forms the main topic of the thesis is outlined and in the last part of this chapter, the set-back irregularity criteria in seismic codes are evaluated. The Turkish Seismic Code defines the set-back irregularity as; 'A geometric irregularity that is considered to exist where the horizontal dimension of the lateral force resisting system in any story is more than %150 of that in an adjacent story'. One story penthouse need not be considered. The ratio of the base width of the set back building, b, to the width of the tower part, a, is named as the criterion of set back buildings according to ABYYHY- 1996. If the ratio of set-back buildings is b/a >1.50, the analysis of the lateral force resisting systems can not be used as 'Equivalent Static Loads' according to the Turkish Seismic Code principles. Whereas, dynamic analysis is required. XVII In the sixth chapter, the 'Numerical Experimentation' method on the predetermined typical structures is explained. The Numerical Experimentation Method is applied to all predetermined typical structures separately for each soil type given in ABYYHY-1996. For each soil type, earthquake designs of the typical structures selected for this study are made using both equivalent static load approach and the dynamic load approach that are recommended in the code. Primarily, analyses are made using Equivalent Static Earthquake Load Procedures and design momente, Ms, are calculated for each critical section. Then, the same examples are resolved using the Modal Superposition Procedure which is the dynamic method recommended in the specifications and the design moments, MD,, are calculated. The ratio of the bending moments obtained from the equivalent static force procedures, and from the dynamic design, at any section, is named as 'Static Safety Factor' (abbreviated as SGK). (Equation 6.1) SGK = ^- (6.1) MD Calculated SGK values, together with their mean values (SGKort) and the standard deviations (SS) form the basis of the comparison of the considered method. This ratio being greater than 1, reveals the reliability of the 'Equivalent Statical Load Method'. Values smaller than 1, indicate that the Equivalent Load Method is not safe enough. SGK values calculated for the columns and beams are the weighted mean values, given Equation 6.2, which are calculated for the overall structure. ZM SGKort=^-±- (6.2) The standard deviations (SS) of SGK values found for each section are calculated as given in Equation 6.3, SS2 = Z Md (SGK ~ SGK°n ) (6 3) T.MD XVUl The calculated standard deviations show the amount of deviation of the obtained safety factor at each critical section of the structures from the mean value. In the seventh chapter, the application of the numerical experimentation method of the typical set-back buildings is presented and the results are evaluated. Each typical structure is arranged as 8, 16, 24 stories. With the changes in geometrical and stiffness properties the numbers of the typical structures are increased. In the first part of this chapter, the ratios of the horizontal dimensions (b/a) of the set-back building are changed. In the second part, the numbers of the set-back stories are increased at each solution. That is, the ratios of the vertical dimensions h/H (h- the height of the set-back stories, H- the height of the set-back building) are changed. Additionally, the sections of the structures where SGK values are smaller than 1 (SGK<1 - Critical Sections), are marked. Finally in the last chapter, the results of the numerical experimentation are evaluated. By the application of the numerical test procedure, a large variety of set-back structures have been tested and a number of interesting results for set-back structures have been produced. The most important of these are listed as follows : 1- The set-back irregularity is defined only according to its geometrical dimensions in ABYYHY and in most contemporary seismic regulations and the code for multi-story buildings. And in almost all seismic codes 'Dynamic Analysis' is demanded for set back buildings. But it is revealed that, for the set-back structures which are not fit to the geometrical criterion of ABYYHY- 1996, the obtained individual SGK values at almost all of the critical sections, as well as all the overall weighted average SGKort values, are found to be greater than unity. The SGK values are only smaller than one (SGK<1 - critical sections) at the beams in the middle span of the set-back stories. That reveals the reality that the 'Static Equivalent Loading' is both safe and practicable. And the geometrical criteria in ABYYHY do not exactly explain the 'Set-Back' irregularity. When the examples and results are examined in chapter 7, it is seen that the explanations of set-backs are not depended only on the geometrical dimensions. The results show that the irregularity may depend on the stiffness distribution along the elevation of the structure. For this reason, the relative story displacements are examined. According to the ratio of the relative story displacements, 'KKDO', values for each adjacent story are calculated. The KKDO values in the level of the set-back story increase. This increase depends on the ratio of the stiffness along the elevation of the set-back building, not on the geometrical dimensions. When the ratio increases the number of the critical sections (SGK<1) increases, too. When KKDO values are XIX smaller than a certain value, the critical sections do not occur. For example, if the values of KKDO are approximately as follows : 8-story set-back buildings - ? KKDO < 2.00 16-story set-back buildings ? KKDO < 1.90 24-story set-back buildings - ? KKDO < 1.70 the 'Equivalent Static Load' method is safer than the 'Dynamic Analysis'. As a result, KKDO might be a 'Criterion' on set-back buildings. However, the value of KKDO depends on the number of stories, approximately when it is a smaller than 1.50 (KKDCK1.50), the critical sections (SGK<1) disappear. 2- The results from the second part of Chapter 7 show that; when the numbers of set back stories are increased, the critical sections (SGK<1) disappear. The results of the study reveal that permission may be given to more stories, not only to one penthouse as stated in ABYYHY-1996. 3- 'Dynamic Analysis' is not a 'Punitive Measure' for set-back irregularity. The 'Compulsory Dynamic Analysis' appears to be an economical measure rather than a punitive, because SGK values are only smaller than 1 at the beams in the middle span of the set-back stories. At the other sections of the overall structure the 'Dynamic Analysis' results are smaller than these 'Equivalent Static Load' methods. 4- A practicable analysis method for set-back buildings is proposed as; the design moments of the critical sections (SGK<1) which occur at the middle span of set-back stories can be expanded to one. 5- The 'Set-Back' irregularity is a very contraversial topic. So, some further study on this topic is recommended.
Investigation of set-backirregularity in earthQuake-resistant design of multi-story structures
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Deprem; Yüksek yapılar; Earthquakes; High structures